ENFORCEMENT AND LEGAL SANCTIONS OF SEMARANG CITY LOCAL REGULATION NUMBER 2 OF 2022 REGARDING FOOD SAFETY FOR VENDORS OF ELEMENTARY SCHOOL SNACKS IN SEMARANG CITY - Nur Imamah Hawa; Dyah Listyarini; Adi Suliantoro (Universitas Labuhanbatu, 2024)
Healthy snacks for elementary school students need to meet nutritional standards to support their growth and development. However, many snacks in elementary schools do not comply with the expected cleanliness and nutritional standards. This research explores the implementation and penalties associated with Regional Regulation No. 2 of 2022 in Semarang. The lack of supervision over snacks can have a negative impact on students' health, potentially affecting their future well-being. Although the local government has carried out its duties according to the regulations, the limited awareness of the community and elementary school students regarding the cleanliness and nutritional literacy of snacks remains a challenge. The processing of food and raw materials that are not clean can threaten children's health. Therefore, there is a need for increased understanding and awareness of the importance of cleanliness and nutrition in snacks for elementary school students in accordance with applicable regulations.Keywords: Regional Regulation; Enforcement; Elementary School; Snacks; Sanction.